Effect of selenium-yeast feeding on amelioration of simulated heat stress and reproductive performance in Malpura ewe under semi-arid tropical environment - DE, KALYAN; SAHOO, ARTABANDHU; SHEKHAWAT, INDU; KUMAWAT, PANKAJ; KUMAR, DAVENDRA; NAQVI, S M K (The Indian Journal of Animal Sciences, 2017)
The present study was carried out for 35 days to assess the effect of selenium (Se)-yeast feeding on amelioration of simulated heat stress and reproductive performance of sheep. Twelve adult Malpura ewes were divided into two groups viz., G1 (n=6, control) and G2 (n=6, Se-yeast supplemented). The ewes of G2 were provided with Se at 0.3 mg/kg feed dry matter (DM) through Se-enriched yeast (Saccharomyces cerevesiea). The animals were stall fed individually with a diet consisting of 70% roughage (Cenchrus ciliaris) and 30% concentrate. All the ewes were estrus synchronized using intra-vaginal progesterone sponges+eCG protocol. To simulate heat stress, the ewes were kept inside the psychometric chamber and were exposed to different temperature at different hours of the day. Supplementation of Se-yeast had no significant effect on physiological response. Higher glucose and a lower protein level was found in the Se-yeast supplemented group under heat stress. Plasma metabolic hormone and cortisol level was higher in G1 as compared to Se-yeast supplemented ewes. Plasma glutathione peroxidase (GPx) was 10.62% higher in G2 as compared to the G1. Estrus percentage and estradiol level was higher in G2 as compared to the G1. From the findings of the present experiment, it is pertinent to conclude that the level of Se enriched yeast fed in this study have limited potential to ameliorate heat stress. However, different doses of Se could be tried in sheep to improve resilience against heat stress.